THE IMPORTANCE OF LEXICAL INTERFERENCE IN THE STUDY OF A FOREIGN LANGUAGE - To'rayeva, Muborak (Журнал иностранных языков и лингвистики, 2021)
The article discusses the importance of lexical interference in the study of a foreign language. It defines lexical interference as the borrowing of lexemes of a foreign language in bilingualism, which is expressed either in transferring in a phonemic sequence from language to another, or in shifts in the structure of the meaning of the lexeme of the native language, or in formations scalped according to models of foreign words.